HERMENEUTIC CITIZENSHIP (A FOCUS THAT GOES TRANSCENDS THE MULTICULTURALISM OF THE GLOBAL VILLAGE IN THE SOCIETY OF KNOWLEDGE) (Andamios, Revista de Investigación Social, 2009)
Globalization and migration trigger the “universalism vs. peculiarism” problem. The solutions generated so far haven’t been sufficient. Multiculturalism doesn’t save relativism. Tolerance is not enough for Interculturalism. Multiculturalism isn’t explicit as to how to “take in” the differences. The Society of Knowledge brings a new notion of Citizenship that hermeneutically melts diverse horizons of significance; it achieves an empathic comprehension that affirms the originality, authenticity and social peculiarity, as well as preserving individual identity.
Keywords: Universalism; ethnocentrism; multiculturalism; society of knowledge; hermeneutic